Control and Prevention of Transmission of Skin Infections - Inda Astri; Fitriani; Dewi (Conferences of Medical Sciences Dies Natalis, 2020)
Skin infections are the most common skin diseases found in densely populated, slum neighborhoods including boarding schools / pesantren. Skin infections can occur at any age, closely related to environmental influences, hosts and causative agents. Common skin infections in congested conditions are scabies infestations, dermatophytosis and pyoderma. Knowledge of skin infection symptoms, personal and environmental hygiene are also determinants of disease transmission. Some efforts to control and prevent the transmission of skin infections include screening for infectious diseases, treatment and providing counseling about skin diseases and ways to prevent transmission.